2019
DOI: 10.33899/ijvs.2019.125512.1034
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing-based phylogenetic-study of Babesia spp detected in tick tissues in Al-Diwaniyah province, Iraq

Abstract: Our study purpose was to investigate the evolution of Babesia spp isolated from tissues of ticks that were found on 150 cows in Al-Diwaniyah province, Iraq. To fulfill the required purpose, sampling of 10 ticks was performed from each infested cow. These obtained ticks were morphologically recognized first, and then they were introduced to Lab investigation that was started with crushing the tick tissues to extract the genomic DNA of the Babesia spp. The DNA was then applied to polymerase chain reaction (PCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…We suggested that our strains might have descended from the ancestor of the Americanisolates, and that there are certain factors might play a role in distribution of this ancestor around the world such as moving of the animals and humans in addition to importation and exportation processes. Surprisingly, the local strains of our study were incompatible with that detected previously in cattle-feeding ticks in Al-Diwaniyah province, Iraq (11), demonstrating that there many strains of B. bovis circulate in Iraqi cattle livestock and their infested-ticks. Also, uncontrolled importation of domestic and wildlife animals might participate in existence of new isolates/strains in Iraq.…”
Section: Figure 1tick Distribution Among Body Regions Of Infested Cacontrasting
confidence: 89%
See 2 more Smart Citations
“…We suggested that our strains might have descended from the ancestor of the Americanisolates, and that there are certain factors might play a role in distribution of this ancestor around the world such as moving of the animals and humans in addition to importation and exportation processes. Surprisingly, the local strains of our study were incompatible with that detected previously in cattle-feeding ticks in Al-Diwaniyah province, Iraq (11), demonstrating that there many strains of B. bovis circulate in Iraqi cattle livestock and their infested-ticks. Also, uncontrolled importation of domestic and wildlife animals might participate in existence of new isolates/strains in Iraq.…”
Section: Figure 1tick Distribution Among Body Regions Of Infested Cacontrasting
confidence: 89%
“…Findings of PCR assay indicated that both B. bovis and B. bigemina were circulating significantly in tick vectors. In Iraq, B. bovis was the only Babesia species isolated from tick samples of infested cattle (11). Therefore, this study was the first report of B. bigemina in ticks infested cattle.…”
Section: Figure 1tick Distribution Among Body Regions Of Infested Camentioning
confidence: 71%
See 1 more Smart Citation
“…But the constructed phylogenetic tree revealed that one sequence (B. bigemina Nar/Pak-8) clustered in a different sub clade, denoted to be genetically different from other isolates collected from Narowal. This tree was as similar as constructed within a study that conducted in South Africa in 2013 (Mtshali et al, 2013;Hajeel and Al-Fatlawi et al, 2019). The tree is drawn to scale, with branch lengths measured in the number of substitutions per site.…”
Section: Discussionmentioning
confidence: 99%
“…Transferring the samples in a cold box to the parasitology lab of the College of Veterinary Medicine, Al-Qadisiyah University, gross examination of the samples grossly for collecting the adults, isolated worms were taken by forceps to diagnose species of parasites, depending on the diagnostic characteristics described by (1,15). Molecular identification of the nematodes uses extracted of 20 rDNA isolates and traditional PCR technique with higher purity of DNA (16)(17)(18), PCR master mix prepared by using AccuPower® PCR PreMix Kit and this master mix done according to company instructions included: DNA template 5µl, Forward primer 1.5µl, Reveres primer 1.5µl and PCR water 12µl. The PCR primers used in this analysis to the amplify ITS2rDNA gene of P. skrjabini, it is being designed according to (9), while COX1mtDNA gene was prepared as (non-degenerate primer) according to the molecular study of other Spirurida (19), these primers were produced from Bioneer company, Korea as following table 1, and reaction conditions of PCR for amplification showed as in the table 2.…”
Section: Methodsmentioning
confidence: 99%